EFFICIENT REBROADCASTING USING TRUSTWORTHINESS OF NODE WITH NEIGHBOUR KNOWLEDGE IN MANET - Shailesh P. Patil; Pankaj R. Chandre (International Journal of Innovations in Engineering Research and Technology, 2021)
Mobile Ad hoc network is an infrastructure less communication network with limited resources. To maintain virtual infrastructure for communication broadcasting mechanisms is used. Due to lack of energy efficiency in Mobile Ad hoc network, there is a need to develop an efficient broadcasting model which enhances energy efficiency. Also nodes with malicious behaviour cause an internal threat that disobeys the standard and degrades the performance of routing protocols. This paper introduced an enhanced rebroadcasting algorithm, where rebroadcasting decision for next hop is immediate or delayed on the basis of trust value and energy level of particular node. This approach helps to decrease number of rebroadcast, energy consumption and also enhances security.